A systematic review and meta-analysis to inform cancer screening guidelines in idiopathic inflammatory myopathies. (18th February 2021) - Oldroyd, Alexander G S; Allard, Andrew B; Callen, Jeffrey P; Chinoy, Hector; Chung, Lorinda; Fiorentino, David; George, Michael D; Gordon, Patrick; Kolstad, Kate; Kurtzman, Drew J B; Machado, Pedro M; McHugh, Neil J; et al.
Abstract: Objectives: To identify clinical factors associated with cancer risk in the idiopathic inflammatory myopathies (IIMs) and to systematically review the existing evidence related to cancer screening. Methods: A systematic literature search was carried out on Medline, Embase and Scopus. Cancer risk within the IIM population (i.e. not compared with the general population) was expressed as risk ratios (RR) for binary variables and weighted mean differences (WMD) for continuous variables. Evidence relating to cancer screening practices in the IIMs were synthesized via narrative review. Results: Sixty-nine studies were included in the meta-analysis. DM subtype (RR 2.21), older age (WMD 11.19), male sex (RR 1.53), dysphagia (RR 2.09), cutaneous ulceration (RR 2.73) and anti-transcriptional intermediary factor-1 gamma positivity (RR 4.66) were identified as being associated with significantly increased risk of cancer. PM (RR 0.49) and clinically amyopathic DM (RR 0.44) subtypes, Raynaud's phenomenon (RR 0.61), interstitial lung disease (RR 0.49), very high serum creatine kinase (WMD −1189.96) or lactate dehydrogenase (WMD −336.52) levels, and anti-Jo1 (RR 0.45) or anti-EJ (RR 0.17) positivity were identified as being associated with significantly reduced risk of cancer. Nine studies relating to IIM-specific cancer screening were included. CT scanning of the thorax, abdomen and pelvis appeared to be effective in identifying underlying asymptomatic cancers. Conclusion: Cancer risk factors should be evaluated in patients with IIM for risk stratification. Screening evidence is limited but CT scanning could be useful. Prospective studies and consensus guidelines are needed to establish cancer screening strategies in IIM patients.